Starlikeness and related properties of certain integral operator for multivalent functions - MOHAPATRA , Ram Narayan; PANIGRAHI , Trailokya (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
In this paper, the authors introduce a new general integral opera- tor for multivalent functions. The new sufficient conditions for the operator Jp,γ,g (f1, f2, ..., fn) when γ = 1 is determined for the class of p-valently star- like, p-valently close-to-convex, uniformly p-valent close-to-convex and strongly starlike of order δ (0 < δ ≤ 1) in U. Our results generalize the results of Frasin [7]. Mathematics Subject Classification (2010): 30C45.